Regulation A+ and other alternatives to a traditional IPO : financing your growth business following the Jobs Act - Feldman, David N., 1960- (Bloomberg financial series., 2018)
This book delves into the details of the new SEC rules under the JOBS Act of 2012 to examine the benefits and pitfalls for entrepreneurs and investors. Written by the 'Godfather of Reg A+, ' this book breaks down the complex details of Regulation A+ and other alternative funding methods to help small businesses determine how best to go public and raise capital. A traditional IPO comes with barriers that can be insurmountable for a small company seeking to enter the public markets; thus far, reverse mergers have provided a challenging 'back door' to the market, but Regulation A+ re-opens the front door to allow small cap companies to raise capital while keeping offering and compliance costs manageable in a way not possible with a traditional IPO. More complex than simple crowdfunding, yet just as accessible by all investors, Regulation A+ is a step up for entrepreneurs at any stage wanting to go public where Wall Street meets Main Street.